Propuesta y aplicación metodológica para el cálculo del índice de salud a partir de la percepción y su acercamiento a la situación real del individuo (2019)
This thesis addresses utility measure in order to quantify the Health Index. This item is a necessary input for the health economics assessment, and is treated as a multi criteria decision-making –MCDM- issue. This work proposes a methodology with hybrid methods that combine the Hierarchical Analytical Process -AHP- , AHP extended by D-numbers and fuzzy AHP -FAHP- with the Technique for Order of Preference by Similarity to Ideal Solution -TOPSIS- in order to elicit preferences and measure the Health Index. Theoretical and methodological grounds are obtained through a systematic meta-narrative review on theories, concepts and methods, as well as an analysis of the regulatory system and techniques applied in Colombia for health technology and economics assessment. In order to implement the proposed methodology, an empirical study is carried out with data collection fieldwork using the EQ-5D-5 international survey, incorporating sociodemographic questions and the pairwise comparisons matrix for health dimensions. The EQ-VT protocol to obtain preferences by composite time trade off -cTTO- and the visual analog scale -VAS- for individual perception about health status are used. Weights for the several health states were obtained using the proposed hybrid methods, cTTO and VAS. Then a comparison is made using quality adjusted life years -QALYS-, weights and the hierarchical structure of the health dimensions. This exercise shows that there are methods with little complex mathematical algorithms that produce consistent results and adjust adequately to the utilities. These methods do not require long processes and training costs to the interviewers and can be applied to specific populations that have been treated by different health programs. In addition they make it possible to eliminate bias imposed by duration in better and worse states of health, and they preserve ordinal preferences expressed in consistent comparison matrices, which allows preserving the range in a strong way.